Crystallization of biologically active hemagglutinin-neuraminidase glycoprotein dimers proteolytically cleaved from human parainfluenza virus type 1. - Takimoto, T (1992)
We isolated, purified, and characterized the hemagglutinin-neuraminidase (HN) of human parainfluenza virus type 1, with the ultimate goal of producing crystals suitable for three-dimensional X-ray structure analysis. Pronase was used to cleave the globular head of the HN molecule directly from virus particles, forming HN monomers and dimers. The purified dimers retained neuraminidase and hemadsorption activity and were recognized by 14 anti-HN monoclonal antibodies, demonstrating intact HN antigenic structure and function. N-terminal sequence analysis of the dimers showed that cleavage had occurred at amino acid 136 or 137, freeing the C-terminal 438 or 439 amino acids. On electron micrography, the dimer appeared as two box-shaped structures, each approximately 5 by 5 nm. When the purified HN dimers were crystallized in hanging drops by vapor diffusion against 20% polyethylene glycol 3350, they formed both rectangular plates and needlelike crystals. The rectangular crystals diffracted X-rays, indicating an ordered atomic structure. However, the resolution was approximately 10 A (1 nm), insufficient for three-dimensional structural analysis. Experiments to improve the resolution by increasing the size and quality of the crystals are in progress.